Impact of social background and behaviour on children's thermal comfort. (September 2017) - Montazami, Azadeh; Gaterell, Mark; Nicol, Fergus; Lumley, Mark; Thoua, Chryssa
Abstract: This study investigates whether children's thermal perception at home and their dominant behaviour to achieve thermal comfort are related to their socio-economic background and contribute to their thermal perception at school. The indoor operative temperatures of 27 classrooms were collected during the cooling season of 2014–2015 from eight primary schools located in the West-Midlands, UK. The perception of 662 students aged between 8 and 11 years old about thermal comfort at both home and school and their dominant behaviour in achieving thermal comfort within school was established through questionnaires. Behaviour was studied under two categories of personal behaviour (e.g. adjusting clothing) and environmental behaviour (e.g. asking teachers to open windows). The socio-economic background of the children was investigated through available data. This paper reveals a relationship between children's socio-economic background and their perception of thermal comfort in primary schools. Results indicate that the behaviour of children differs depending on their socio-economic background. There is a strong relationship between children's thermal perception at home and at school among those that come from less privileged backgrounds. Those from less privileged backgrounds also find their classrooms warmer compared to the other children. Highlights: Children's thermal perception is not only related to a classroom's indoor temperature. There is a relationship between children's thermal perceptions at school and home. Children's thermal behaviour is affected by their socio-economic background. Children from privileged backgrounds use personal changes to achieve thermal comfort. Children from non-privileged backgrounds use environmental changes to achieve comfort.